Micromachining: technology for the future. (1st June 2007) - Gowri, S.; Ranjith Kumar, P.; Vijayaraj, R.; Balan, A.S.S.
A comprehensive review of the literature, mostly of last 15 years, that is enhancing our understanding of the mechanics of the rapidly growing field of micromachining has been provided. The paper focuses only on tool based micromachining processes, namely, micro cutting and micro Electro Discharge Machining (micro EDM). The main technological developments associated with cutting tools, tool materials, process conditions, experimental work, surface integrity and applications which have led to present day advancement are given detailed consideration in this paper.